(untitled) (Research, Society and Development, 2021)
Six waterfalls were studied, all in the Cerrado Biome, three located in the county of Mineiros/Goiás state and three in the county of Nova Xavantina/Mato Grosso state in order to analyze the distribution of species in the environments associated with waterfalls. We found 102 bryophytes species (68 genera and 37 families). Lejeuneaceae was the richest one (14 species). The habitats with waterfall influence sampled were “vereda” (upstream), waterfall (fall creek) and gallery forests (downstream), they are differentiated specially by its humidity and shading. The waterfall influences in the habitats related show increase in richness and composition, and change the community in relation to the life forms of the colonists species. The waterfalls of the two counties have floristic differences in composition, with the waterfalls of Nova Xavantina show influence of the Amazon Biome and Mineiros with Pantanal biome.